Singapore perspectives 2015: Choices - SOON, Carol (Institutional Knowledge at Singapore Management University, 2016)
Singapore reaches an important milestone in its national development in 2015 when it celebrates its 50th year of independence. It has earned many accolades for the progress it has made in governance, the economy and societal development. However, with changing demographics, resource constraints and the emergence of regional competitors, Singapore's future is fraught with uncertainty.The book is a collection of papers presented at Singapore Perspectives 2015 by leading thought leaders and eminent speakers, reflecting on the critical decisions made in Singapore's past so as to envision strategic paths that the country should take in the future.The contributors include experts in their fields: Ambassador Bilahari Kausikan, Professor Evelyn Goh, Professor Tan Kong Yam, Professor Linda Lim, Professor Kishore Mahbubani, Tong Yee, Vikram Khanna and Associate Professor Eugene Tan. The inter-generational dialogue session with Deputy Prime Minister Teo Chee Hean and Minister in the Prime Minister's Office and Secretary-General of the National Trades Union Congress Chan Chun Sing carries the central theme of looking at the choices Singapore made in the past and the choices that have to be made moving forward.In line with reflecting on Singapore's past, the book will include a full report on a survey of 1,500 Singaporeans' perceptions of 50 historical events from independence to now.